IRRITATION TEST OF BAWANG DAYAK (Eleutherine bulbosa(Mill.) Urb.) EXTRACT CREAM WITH HUMAN PATCH TEST METHOD - Syahrida Dian Ardhany; Susi Novaryatiin; Mohammad Rizki Fadhil Pratama; Zulkhurnain Utar (Universitas Muhammadiyah Magelang, 2021)
Topical agents indicated for the treatment of acne have the potential to cause irritation or allergic contact dermatitis. This study investigates the irritancy potential of anti-acne cream of bawang dayak (Eleutherine bulbosa (Mill.) Urb.) previously tested for microbiological effectiveness with the lowest concentration of 5% and the highest concentration of 20%. The method used in this study is the human patch test. A total of 20 volunteers were recruited for the patch test study, testing the cream. The result showed that all volunteers did not experience irritation both in the 5% or 20% bawang dayak extract cream formulations. However, the interview results were found that some volunteers experienced a slight itching without any significant skin adverse reactions on the cream application. Therefore, based on these initial findings it can be safely concluded that the cream of bawang dayak does not cause significant skin adverse reaction and good enough for further development for anti-acne cream dosage form.